2017
DOI: 10.4103/jips.jips_10_17
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal response of or-al-associated candidal reference strains (American Type Culture Collection) by supercritical fluid extract of nutmeg seeds for geriatric denture wearers: An in vitro screening study

Abstract: Objectives:Since time immemorial, plants have continued to play a predominant role in the maintenance of human health as sources of medicinal compounds. Several effective antifungal agents are available for oral Candida infections; the failure is not uncommon because isolates of Candida albicans may exhibit resistance to the drug during therapy. The present study aimed to identify an alternative, inexpensive, simple, and effective method of preventing and controlling the candidal infection.Methodology:All the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…Such findings are in agreement with the results presented in this work, demonstrating the potential antifungal effect of the oil against several species of fungi. The antifungal action of Myristica fragrans essential oils has also been demonstrated against strains of Aspergillus niger, Fusarium axysporum, Pinicillium glabrum, Rhizopus oryzae and Mucor recemosus (28) as well as against Candida albicans (52). These results corroborate the present study, where antifungal activity against Rhodotorula mucilaginosa was also proven (Table 4).…”
Section: Resultssupporting
confidence: 91%
“…Such findings are in agreement with the results presented in this work, demonstrating the potential antifungal effect of the oil against several species of fungi. The antifungal action of Myristica fragrans essential oils has also been demonstrated against strains of Aspergillus niger, Fusarium axysporum, Pinicillium glabrum, Rhizopus oryzae and Mucor recemosus (28) as well as against Candida albicans (52). These results corroborate the present study, where antifungal activity against Rhodotorula mucilaginosa was also proven (Table 4).…”
Section: Resultssupporting
confidence: 91%
“…Major constituent in essential oil of M. fragrans are myristicin, safrole, pinene, isoeugenol, 4terpenol as reported by Alcazar-Fuoli and Mellado [54]. Various studies have also reported the presence of neolignan and macelignan in M. fragrans extract [14,42]. The quantitative and qualitative divergence of plant constituents may be due to the geographical, climatic, and soil conditions, which in turn may affect the composition and/or synthesize new secondary metabolites from the same plant species [55].…”
Section: Discussionmentioning
confidence: 96%
“…The present study confirmed the presence of alkaloids, steroids, tannins and terpenoids in M. fragrans extract. However, Iyer et al reported the absence of terpenoids in their extracts [42]. This variation may be attributed to the plant sources, climatic conditions and the extraction methodology [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This problem seems to be particularly important if we consider that a large number of denture wearers suffer from fungal infections in the oral cavity [ 27 , 28 , 29 , 30 , 31 ] and that the presence of soft liners may promote Candida colonization [ 20 ]. It is also known that the use of medications in older people may have negative outcomes [ 32 ] and frequent use of antifungal drugs may lead to drug resistance of pathogenic microorganisms [ 33 ]. Thus, to avoid complications related to the growth of microorganisms, denture base materials as well as soft denture lining materials with increased resistance against pathogenic fungi are required.…”
Section: Introductionmentioning
confidence: 99%